The Development Pattern of Early Age Children’s Motor Skills (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
This study was aimed at identifying the pattern of early age children’s motor skills development. By acknowledging the pattern, a program was expected to be developed to improve the early age children’s motor skills. Motor skills are not only closely related to children’s physical abilities and intelligence but they are also associated with children’s psychological aspect. Denver Development Screening Test (DDST) was used as the research instrument. Then, the obtained data were analyzed by using descriptive statistic. The data and information were collected from respondents using observation sheets. After collected, the data were explained descriptively. The population of this study involved the early age children in the kindergartens. Moreover, in order to prevent distortion of data, the data collection employed Stratified Random Sampling technique in which population is grouped into five based on regencies and sub-grouped based on districts, so the groups of population were homogenous. The research findings present the early age children’s motor skills development pattern. In general, the results are: social behavior aspect is categorized as very good, and its percentage point is 57.14%; language aspect is categorized as very good, and its percentage point is 61.91%; gross motor skill aspect is categorized as very good, and its percentage point is 71.44 %; and the fine motor skill aspect is categorized as very good, and its percentage point is 57.14%. Based on the findings, it can be inferred that children’s motor skills development is an important part in the human life span. On the other hand the more important thing is how children innate motor skills can be optimized in a program suitable with children needs, so they can benefit from doing appropriate physical activities